Isolation and characterization of in vitro culture of hair follicle cells differentiated from umbilical cord blood mesenchymal stem cells - Bu, Zhang-Yu (Exp Ther Med, 2017)
The present investigation explored the in vitro culture, isolation and characterization of hair follicle cell differentiation from umbilical cord blood mesenchymal stem cells (MSCs). Flow cytometry was used to obtain MSCs from the isolation and purification of human umbilical cord blood MSCs. Culture suspension of hair follicle organ was centrifuged and the supernatant used in the culture medium of MSCs, and the entire process of induced differentiation was recorded by photomicroscopy. The expression level of surface marker CK15 of hair follicle cells obtained from induced differentiation was detected with immunofluorescence. RT-PCR method was used to further detect the difference in expression of CK15 between hair follicle cells and umbilical cord blood MSCs, and statistical analysis was carried out. CD44(+)CD29(+) double-labeled cells accounted for 50.8% of all the samples of umbilical cord blood MSCs in this study. The diameter of hair follicle cells differentiated from umbilical cord blood stem cells reached 800×10(−3) mm after 3 weeks of cell culture. Based on the detection and colocalization of CK15 expression in induced hair follicle cells, the overlap ratio between CK15 and nuclei reached 83% in hair follicle cells, which was obviously higher than that in umbilical cord blood stem cells. The difference had statistical significance (P<0.05). In conclusion, hair follicle cells can be successfully differentiated from umbilical cord blood stem cells by using the supernatant from hair follicle cells. This method can be used for high-speed induced differentiation with high purity, which is promising for clinical application.